SARS-COV-2 MRNA vaccine-associated cutaneous vasculitis - Erol, Vedat Buğra; Can, Meryem (Kare Publishing, 2023)
During the coronavirus disease 2019 pandemic, global approach was to isolate populations with quarantine procedures to reduce the spread of this deadly virus until effective treatments are found or vaccines are developed. mRNA-based vaccines became available in the United States in March 2020. The Food and Drug Administration even issued an Emergency Use Authorization for individuals 16 years and older in December 2020. However, these rapid developments have brought along other problems such as possible side effects. As we develop and test a new treatment, it became clear how important side-effect management is. Here, we present a case of cutaneous vasculitis that developed on the fourth day of SARS-CoV-2 mRNA vaccination. The patient was successfully treated with medium-dose methylprednisolone.
Keywords: COVID-19 Vaccine; Cutaneous Vasculitis; Leukocytoclastic Vasculitis; mRNA Vaccines; SARS-CoV-2 Virus